Hypofibrinogenemia caused by tigecycline use in a patient with acute cholecystitis: a case report and review of the literature - Ayhan, Müge; Can, Ferda; Karaahmetoğlu, Selma; Güner, Rahmet (The European Research Journal, 2021)
Tigecycline is the first member of glicylcycline class of antibiotics, which has a broad spectrum of action. In previous reports, coagulopathy and hypofibrinogenemia caused by tigecycline use was described. We aimed to present a case of hypofibrinogenemia in association with tigecycline use. A 79-years-old male was admitted to medical intensive care unit for acute cholecystitis and acute renal failure. He had no history of coagulation disorder. He was receiving meropenem for septic shock on the admission. On the 7th day of meropenem, his infection didn’t improve and fever continued. Because of that tigecycline was added to treatment. Patient’s infection parameters improved, his fever dropped under treatment, but his prothrombin time, international normalized ratio and activated partial thromboplastin time levels increased and fibrinogen level decreased (0.96 g/L). Tigecycline was discontinued that day. On the fifth day after cessasion of tigecycline, his fibrinogen levels and other coagulation parameters returned to normal ranges. The mechanisms of coagulopathy and hypofibrinogenemia should be elucidated in futher studies. We strictly suggest, regular monitoring of coagulation parameters in patients receiving tigecycline treatment.